2020
DOI: 10.1016/j.bbih.2019.100011
|View full text |Cite
|
Sign up to set email alerts
|

Whole body vibration elicits differential immune and metabolic responses in obese and normal weight individuals

Abstract: Traditional aerobic exercise decreases the risk of developing inflammatory diseases in both obese and normal weight individuals. The magnitude of the anti‐inflammatory immune response following traditional exercise is reduced and the time‐course is shorter in obese compared to normal weight individuals. Although obesity may affect the ability to engage in traditional exercise, whole body vibration (WBV) has emerged as a more tolerated alternative. The impact of WBV on immune‐mediated inflammation in obesity, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 51 publications
3
22
1
Order By: Relevance
“…Besides insulin therapy and probiotic supplementation, other interventional measures like whole-body vibration, increased exercise, and nutritional changes, which aimed to decrease insulin resistance (IR), improve BG control, and restore intestinal eubiosis, were shown to significantly downregulate LGI by decreasing IL-6, TNF-α, and IL-1-β levels (36)(37)(38)(39)(40). Although there is no direct evidence certifying a protective effect of supplements like Vitamin C, Vitamin D, Zinc, probiotics, and synbiotics on COVID-19 outcomes, we are hypothesizing that preventive measures targeting LGI can lower the propensity to develop severe disease (41)(42)(43)(44).…”
Section: Therapeutic and Preventive Strategiesmentioning
confidence: 99%
“…Besides insulin therapy and probiotic supplementation, other interventional measures like whole-body vibration, increased exercise, and nutritional changes, which aimed to decrease insulin resistance (IR), improve BG control, and restore intestinal eubiosis, were shown to significantly downregulate LGI by decreasing IL-6, TNF-α, and IL-1-β levels (36)(37)(38)(39)(40). Although there is no direct evidence certifying a protective effect of supplements like Vitamin C, Vitamin D, Zinc, probiotics, and synbiotics on COVID-19 outcomes, we are hypothesizing that preventive measures targeting LGI can lower the propensity to develop severe disease (41)(42)(43)(44).…”
Section: Therapeutic and Preventive Strategiesmentioning
confidence: 99%
“…A recent study by Song et al [35] aimed at assessing the possible effects of WBV on immune cell differentiation and inflammatory markers reported significant increases in lymphocyte and Treg cells normally associated with improvements in the inflammation barrier function. Blanks et al [36] also assessed the impact of WBV on the immune system in healthy participants (ages 18-45 y) (14 Hz, 2.5 mm,~2.1 g) with 10 sets of 1 min vibration periods followed by 30 s of standing rest. The authors observed a significant increase in neutrophil percentage and increases in IL-6, a well-known myokine.…”
Section: Immune and Myokine Responses To Wbvmentioning
confidence: 99%
“…Based on the aforementioned evidence, it seems that IL-6 in response to muscle activation (i.e., WBV) has a number of anti-inflammatory benefits including increased anti-inflammatory cytokine production which could contribute to an attenuation of basal inflammation [62,67]. Blanks et al [36] even suggested that WBV enhanced tissue IL-6 sensitivity and hypothesized, based on previous results after acute exercise [64], that this exercise paradigm would increase anti-inflammatory cytokine production (IL-10). This is consistent with a recent pilot study aimed at assessing the efficacy of WBV on inflammatory markers in individuals with chronic obstructive pulmonary disease.…”
Section: Immune and Myokine Responses To Wbvmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to traditional exercise modalities, WBV can elicit beneficial effects on metabolic health. In fact, a single bout of WBV increases circulating concentrations of IL‐6, which correspond with the normalization of glucose and insulin in obese individuals (Blanks et al, 2020). During bouts of traditional exercise, improvements in glucose metabolism are intensity‐dependent (Clark et al, 2003; Richter et al, 1985).…”
Section: Introductionmentioning
confidence: 99%